Dynamic of functional parameters of cardio-vascular system in patients with vertebrogenic pathology after body position changes - Lyzohub, Mykola; Kotulskiy, Igor; Moskalenko, Natalya; Pishchik, Victoriia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Postural hemodynamic reactions are well-known but their dependency on anthropometrics is still not fully studied. A significant amount of surgeries are provided in prone position, so it is important for anesthesiologist to predict specific physiologic changes. Objectives: to study patterns of functional changes in cardiovascular system in patients with vertebrogenic pathology after turning from supine to prone position and the influence of age and body mass index on them. Material and methods: we examined 200 patients of 18–75 y. o.; 118 male and 82 female. In group І there were patients with body mass index ≤ 25 kg/m2 and in group ІІ – patients with body mass index > 25 kg/m2 . Hemodynamics were examined by thoracic rheography in supine position, in prone position 5 min after turning and in prone position 20 min after turning. Results: in patients of group ІІ vs patients of group A we foundnd significantly higher level of systolic BP in 5 min and 20 min after turning to prone position, and diastolic BP, mean BP and peripheral vascular resistance at all stages of study. Stroke volume index and cardiac index were significantly lower at all stages of studied patients of group ІІ. After turning into prone position diastolic BP and peripheral vascular resistance increased by 15,2 % in all patients, but in patients with body mass index > 25 kg/m2 it did not reverse to basal level. Cardiac index changed only in patients of group ІІ. Stroke volume index decreased by 13,6 % in all patients, but in 20 min it became normal only in patients of group І and was low in patients of group ІІ. Conclusions: compensatory reaction of cardiovascular system after turning to prone position depended on age and body mass index. Dependence on body mass index is more significant and anesthesiologist should be aware of these changes when planning anesthesia in prone position.